Des/re-territorialización de prácticas musicales afrocubanas: compositores académicos cubanos de la diáspora de finales del siglo XX y principios del XXI - Iván César Morales Flores (Les Cahiers ALHIM)
This article ponders on the Afro-Cuban work of three composers of the Cuban diaspora at the turn of the century. For this, we turn our attention to the dynamics of des/re-territorialization music-identities that reveal their compositional discourses, seen here as an expression of simultaneous processes of continuity, rupture, miscegenation and transfers of cultural knowledge. Our purpose is to understand the causes by which their compositional discourses show a special link with religious and music-cultural practices of African descent. And, on the other hand, to see how these links in his Afro-Cuban works of the diaspora are expressed aesthetically and musically. The burden of fragmentation, hybridity and multiplicity of geographical spaces that the works of these migrant composers contain, attracts a wide variety of creative positions and strategies; at the same time, it reveals deep relationships of belonging to a ritual and cultural-afro-descendant tradition of unquestionable roots in the Caribbean transcultural environment.